The Impact of Perceived Stress and Psychosocial Factors on Missed Class and Work in College Students. Issue 3 (October 2016) - Thomas, Jenifer J.; Borrayo, Evelinn A.
Abstract : An understanding of how missed class and work are influenced by psychosocial factors is important. The authors collected data from 303 college students through self‐report questionnaires. Moderation analysis indicated that with higher perceived stress, students were more likely to miss class if they were less satisfied with social support and less likely to miss work if they engaged in avoidant coping strategies. College counselors can provide students with skills to enhance academic performance and engagement in academic life.